Inductive proteomics and large dataset collections. Issue 6 (19th June 2015) - Urbani, Andrea; Roncada, Paola; Modesti, Alessandra; Timperio, Anna Maria; Bini, Luca; Fasano, Mauro; Castagnola, Massimo
<x xml:space="preserve">Abstract</x> Inductive reasoning has been the corner stone of a large plethora of proteomics investigations, shifting the a priori paradigm of classical cellular and molecular biology to the experimental observation of protein modulation. These studies are now providing better definitions of their application framework.